Epidemiology and trend of US pediatric burn hospitalizations, 2003–2016. Issue 3 (May 2021) - Armstrong, Megan; Wheeler, Krista K.; Shi, Junxin; Thakkar, Rajan K.; Fabia, Renata B.; Groner, Jonathan I.; Noffsinger, Dana; Giles, Sheila A.; Xiang, Henry
Highlights: The overall mortality rate of pediatric burn patients decreased from 2003 to 2012. Overall median length of stay (LOS) declined. Median LOS was unchanged for those with severe burns. More patients were admitted to hospitals with high pediatric burn patient volumes. High volume hospitals had increases in patients across all levels of burn severity. Abstract: Background: Thermal injury is a leading cause of unintentional pediatric trauma morbidity and mortality. Methods: This retrospective analysis of the 2003–2016 Kids' Inpatient Database (KID) included children <18 years old with a burn principal diagnosis. The objectives were to describe the trend of US pediatric burn hospital admissions and the patient and hospital characteristics of admitted children in 2016. The trends (2003–2012) and (2012–2016) were evaluated separately due to the 2015 implementation of International Classification of Diseases, Tenth Revision (ICD-10). Results: The population rate of pediatric burn admissions decreased by 4.6% from 2003 to 2012, but the proportion of admissions to hospitals with burn pediatric patient volumes ≥ 100 increased by 63.9%. The overall mortality rate of hospitalized burn patients decreased by 48.1%. Median length of stay increased slightly for patients with a burn ≥20% total body surface area (TBSA) but decreased for patients with TBSA burn <20%. From 2012 to 2016, the population rate decreased by 13.4%. In 2016, an estimated 8160 children were admitted with a burn principal diagnosis, and 41.4% transferred in from other facilities. Children age 1–4 years were the most commonly admitted age group (49.7%). Patients with ≥20% TBSA burns accounted for 7.8% of admissions (95% confidence interval [CI]: 5.1–10.4%). Burn-related complications were documented in 5.9% of admissions (95% CI: 4.6–7.1%). Conclusion: Pediatric burn hospitalizations and burn-related mortality have decreased over time. The increases in transfers and admissions to hospitals with high pediatric burn volumes suggest increasing regionalization of care.